GLASSES IN THE D'ORBIGNY ANGRITE - Varela M.E.; Kurat G.; Brandstätter F.; Zinner E.; Métrich N.; Ntaflos T.; Sylvester P. (My University, 2003)
The D'Orbigny angrite contains abundant glasses, a phase which has not been previously reported from any other angrite. Glasses fill in part open druses and intersticial spaces between major silicates, or occur as glass inclusions in olivine.
Keywords: Angrite